Revisited the relationship between vitamin D level and receptors of BsmI- gene polymorphism with the pathogenetic mechanisms of placental dysfunction development - G. S. Manasova; A. A. Zelinsky; N. V. Didenkul; V. V. Artemenko; E. T. Makshayeva (Journal of Education, Health and Sport, 2018)
The role of the calcitriol / vitamin D receptor (VD) endocrine system and the pleiotropic effects of this system in the pathogenetic mechanisms of various diseases development, in particular complications of pregnancy, has attracted researches’ increasing attention in recent years.